SISTEM INFORMASI E-COMMERCE BARANG INTERIOR DESIGN PADA CAKRA FURNITURE BERBASIS WEB DENGAN MODEL FAST: SISTEM INFORMASI E-COMMERCE BARANG INTERIOR DESIGN PADA CAKRA FURNITURE BERBASIS WEB DENGAN MODEL FAST - Effendi, Zara; Sujono (Himpunan Dosen Ilmu Komputer, 2024)
Cakra Furniture 2 is an interior design sales business, Cakra Furniture 2 is the second branch which was only established on January 27 2024 and has been running for several months. The address is Jalan Depati Hamzah, Semabung Baru, Kec. Girimaya, PangkalPinang City, Bangka Belitung Islands 33146. Cakra Furniture 2 sells various interior designs such as kitchen sets, TV backdrops, minibars, cupboards, study sets and others. At Cakra Furniture 2, promotional activities are only via Instagram. Apart from that, the process of collecting data on interior design orders is still done manually and does not utilize an information system, so submitting order and sales reports and creating invoices takes a long time. To answer this problem, research was carried out to design an e-commerce website at Cakra Furniture 2. In this research, the analysis used the FAST model, for tools as a tool to model the designed system, namely using UML diagrams, while for data collection using interview and observation techniques. The results of this research are in the form of a system design that is used as a reference for building an e-commerce system that can simplify and improve the owner's or customer's ability to carry out sales transactions